2019
DOI: 10.1021/acs.chemmater.9b03327
|View full text |Cite
|
Sign up to set email alerts
|

Acceptor Gradient Polymer Donors for Non-Fullerene Organic Solar Cells

Abstract: In organic solar cells, maximizing the open-circuit voltage (V OC ) via minimization of the ionization energy or electron affinity offsets of the blended donor and acceptor often comes at the expense of achieving a considerable amount of short-circuit current (J SC ). To explore a hypothesis for the design of materials that may circumvent this tradeoff, eight structurally similar polymers were synthesized consisting of a fluorinated/non-fluorinated benzothiadiazole (BTDF/BTD) strong acceptor moiety, a thiophen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 88 publications
0
10
0
Order By: Relevance
“…Recently, research has focused on non-fullerene acceptors (NFAs) in OSCs because of their advantages, including greater optical, electrochemical, and structural flexibility compared to their fullerene counterparts ( Lin et al, 2015 ; Nielsen et al, 2015 ; Hou et al, 2018 ; Zhang et al, 2018a ). In 2019, Reynolds’s et al reported a series of polymers by minimal structure modification with varying electron donors ( Figure 1D ) ( Jones et al, 2019 ). These polymers are consisted of a fluorinated/non-fluorinated benzothiadiazole strong acceptor moiety, a thiophene ester weak acceptor, and various donor units composed of bithiophene, biEDOT, and benzodithiophene to form six acceptor gradient and two non-gradient polymers.…”
Section: Organic Solar Cellmentioning
confidence: 99%
“…Recently, research has focused on non-fullerene acceptors (NFAs) in OSCs because of their advantages, including greater optical, electrochemical, and structural flexibility compared to their fullerene counterparts ( Lin et al, 2015 ; Nielsen et al, 2015 ; Hou et al, 2018 ; Zhang et al, 2018a ). In 2019, Reynolds’s et al reported a series of polymers by minimal structure modification with varying electron donors ( Figure 1D ) ( Jones et al, 2019 ). These polymers are consisted of a fluorinated/non-fluorinated benzothiadiazole strong acceptor moiety, a thiophene ester weak acceptor, and various donor units composed of bithiophene, biEDOT, and benzodithiophene to form six acceptor gradient and two non-gradient polymers.…”
Section: Organic Solar Cellmentioning
confidence: 99%
“…[ 34–38 ] At present, focusing on designing well performed “acceptor‐donor‐acceptor (A‐D‐A)”‐type small molecular acceptors (SMAs), especially the A‐DA'D‐A structured SMAs, is the mainstream of breaking through the bottleneck of power conversion efficiencies (PCEs), for their photovoltaic properties can be easily tuned by simple synthesis steps. [ 39–45 ] One of the milestones of the SMA based OSC development is the PM6:Y6 systems reported by Zou's group recently, which yields a PCE as high as 15.7% for both conventional structure devices and inverter devices by utilizing the advantages of SMAs on absorption spectra and morphology. [ 46 ] Subsequently, a series of OSC systems based on Y6 or Y6 derivative acceptors have been developed, which further improved the PCE of the OSCs to over 16% rapidly.…”
Section: Introductionmentioning
confidence: 99%
“…D-A polymer with alternating electron-donating (D) and electron-accepting (A) units are the most widely used polymer donors in OSCs because of the ease in fine-tuning frontier energy level and light absorption coverage. [15][16][17][18][19][20][21][22][23][24][25][26][27] Historically speaking, the creation of electron-accepting monomers play a crucial role in the evolution of…”
Section: Introductionmentioning
confidence: 99%